The Best Software Writing I Selected and Introduced by Joel Spolsky - Spolsky, Avram Joel (Apress : Imprint: Apress, 2005)
Frustrated by the lack of well-written essays on software engineering, Joel Spolsky (of www.joelonsoftware.com fame) has put together a collection of his favorite writings on the topic. With a nod to both the serious and funny sides of technical writing, The Best Software Writing I: Selected and Introduced by Joel Spolsky is an entertaining read and a guide to the technical writing literati. The Best Software Writing I contains writings from: Ken Arnold Leon Bambrick Michael Bean Rory Blyth Adam Bosworth danah boyd Raymond Chen Kevin Cheng and Tom Chi Cory Doctorow ea_spouse Bruce Eckel Paul Ford Paul Graham John Gruber Gregor Hohpe Ron Jeffries Eric Johnson Eric Lippert Michael Lopp Larry Osterman Mary Poppendieck Rick Schaut Aaron Swartz Clay Shirky Eric Sink why the lucky stiff.